Jostling for Position: the Future of Regional Power-Sharing and the Role of the Pacific Islands Forum (Glocalism: Journal of Culture, Politics and Innovation, 2016)
The Pacific Islands Forum has long held the title of the most dominant regional association with links in trade, politics and regional security. Following two political coups in the region the PIF was forced to shift its approach to regional governance opting for a more active and hands-on role with its first such mission being the Regional Assistance Mission to Solomon Islands (RAMSI). The role undertaken by the PIF within RAMSI is noteworthy for its shifts and changes with an initially minimalist role morphed into an intermediary role as tensions rose between the major funding donor, Australia, and the host state, Solomon Islands in 2006-07. Although the PIF acted in a mediator role in this instance this has not been the normal role for the institution. This article examines the role the PIF has adopted in managing regional democratic stability through targeted development activities, whether their adopted role is applicable on a wider regional-level scale, and further, through examining key human-security related challenges, such as climate change, where the PIF fits into regional power-sharing institutions in the Pacific Islands of the future.
Keywords: regional power-sharing architecture; mediation; Pacific Islands; democratic transition; state-building